Kewajiban Zakat Pada Perusahaan Dalam Perspektif Hukum Islam - Ervina Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to find out whether companies fall into the muzakki category in Islamic law. And to find out the basis of the company's zakat obligations according to Islamic law. This research was carried out using library research and paying attention to the field (Field Research). Literature study is a process of searching for various literature, the results of studies related to the research to be carried out. Literature study can be likened to a key that will open everything that can help solve research problems. The results of the research show that companies are included in the muzakki category in Islamic law, from the perspective of wealth that must be paid zakat, either as shakhshiyyah i'tibariyyah or as a substitute (representative) for shareholders. This is in accordance with Law of the Republic of Indonesia Number 38 of 1999 concerning Zakat Management, Law Number 23 of 2011 concerning Zakat Management, and the Compilation of Sharia Economic Law. And including the decision of the Third Indonesian Fatwa Commission Ijtima' Ulama in 2009. Wahbah Zuhaili is of the opinion that factories and exploration buildings do not have zakat. The zakat is only on annual profits if it reaches the nishab syar'i and completes one year. And from the point of view of the group that is obliged to pay zakat. Namely Muslim, independent, fully owned, sufficient haul, sufficient nisab. So, a company is not a bukallaf that is burdened with various obligations, including zakat obligations. That the basis for company zakat obligations according to Islamic law is qiyas. Because in general, in corporate zakat there are similarities between activities carried out by companies and commerce, namely by selling or trading the products of a company. And because a company is essentially a business unit whose activity is trading which can take the form of a firm, trading company, CV, cooperative, PT and so on. because it is seen as based on trading or commerce activities. Therefore, the nishab is the same as the nishab for trade zakat, namely 85 grams of gold. Keywords: Zakat, Company, Islamic Law